(untitled) (International conference on multidisciplinary science, 2023)
When determining the focal point of the Surkhandarya dialect zone, the city of Termiz is defined as a weak focal point, which indicates that the dialect of the region is not well studied. In this article, the Denov district dialect of Surkhandarya region is analyzed. The influence of the studied regional dialect on neighboring dialects and, conversely, the influence of the neighboring dialect and the Tajik language on the regional dialect were studied by comparing the morphological features of existing places